Broadening Asia's security discourse and agenda : political, social, and environmental perspectives - Thakur, Ramesh, 1948-; Newman, Edward, 1970- (United Nations University Press, 2004)
Going beyond military threats and state-centric analysis, this publication demonstrates the importance of a broad security agenda that incorporates political, economic, social and environmental dimensions.